Successful transurethral resection of the prostate in ectopic prostate pheochromocytoma: A case report. Issue 17 (April 2020) - Zhou, Jin; Wu, Wen-Feng; Zhang, Wenbin; Xin, Jun; Lei, Wen-Hui
Abstract: Introduction: Most pheochromocytomas of the urinary tract are located in the bladder. However, ectopic prostate pheochromocytomas have rarely been reported. We herein report an unusual case of ectopic prostate pheochromocytoma successfully treated by transurethral resection of the prostate (TURP). Patient concerns: A 44-year-old Asian man with no significant previous medical history such as hypertension, presented to the urologist complaining of palpitations and anxiety on urination for more than 1 month. Diagnoses: Pathological examination confirmed ectopic prostate pheochromocytoma. Interventions: An ectopic prostate pheochromocytoma without definite metastasis was confirmed. The lesion was successfully treated via TURP. Outcomes: All of his symptoms completely and immediately disappeared after surgery. Over a 21-month follow-up period, a repeat abdominal computed tomography (CT) scan did not show any evidence of recurrence. Conclusion: When patients present with symptoms of catecholamine excess on urination, extra-adrenal pheochromocytoma in the prostate should also be considered. TURP may be a viable option for therapy.